Management of Giant Thrombosed Mca Aneurysm: Double Sta-Mca Revascularization - Hernandez-Alvarez, V (Elsevier Inc., 2021)
Giant middle cerebral artery (MCA) aneurysms are rare complex cerebrovascular lesions to treat.1 The management of those aneurysms may be very challenging, despite the introduction of refined microsurgical techniques and the rapid progress in endovascular methods, which often require bypass surgery as part of the strategy.2-4 This approach is particularly relevant to giant, dolichoectatic, and thrombotic aneurysms.5,6 This video shows the surgical strategy and stepwise depiction of the surgical treatment of a complex giant thrombosed aneurysm using a double-barrel superficial temporal artery (STA) to MCA bypass (Video 1). Informed written consent was obtained from the patient and his family. The patient was a 50-year-old man, previously healthy, who presented with headache, memory difficulty, and left-sided involuntary movements for 2 months. Computed tomography scan showed a giant round calcified and heterogeneous lesion compatible with a thrombosed MCA aneurysm. Brain magnetic resonance imaging showed the same lesion with a flow void signal inside in a serpentine fashion and a complete hemosiderin halo. Conventional angiography showed the false lumen and the filling of the distal MCA branches with a certain degree of arterial delay. The lesion was located between M1 and M3 segments of MCA. Extracranial-intracranial STA-MCA bypass was performed. Then we opened the aneurysm sac for decompression and observed the lenticulostriate artery branches arising away from the aneurysm sac. The complete clipping and patency of the anastomosis was validated during surgery by indocyanine green angiography. Postoperative cerebral computed tomography angiography revealed good patency from the STA to the MCA. The patient was neurologically intact without complains. © 2021 Elsevier Inc.